Transportation engineering theory, practice and modeling - Teodorovic, Dusan; Janic, Milan (Butterworth-Heinemann, 2022)
Transportation Engineering: Theory, Practice and Modeling, Second Edition presents comprehensive information related to traffic engineering and control, transportation planning and evaluation of transportation alternatives. The book systematically deals with almost the entire transportation engineering area, offering various techniques related to transportation modeling, transportation planning, and traffic control. It also shows readers how to use models and methods when predicting travel and freight transportation demand, how to analyze existing transportation networks, how to plan for new networks, and how to develop traffic control tactics and strategies. New topics addressed include alternative Intersections, alternative interchanges and individual/private transportation. Readers will also learn how to utilize a range of engineering concepts and methods to make future transportation systems safer, more cost-effective, and "greener". Providing a broad view of transportation engineering, including transport infrastructure, control methods and analysis techniques, this new edition is for postgraduates in transportation and professionals needing to keep up-to-date with the latest theories and models.